Analisis Kemampuan Berfikir Kritis Mahasiswa Pendidikan Fisika terhadap Pengelolaan Sampah Menjadi Refuse Derived Fuel (RDF) dengan Perlakuan Biodrying - Ifadatul khikma; Sudarti Sudarti; Yushardi Yushardi (LPPM UNIVERSITAS PGRI SILAMPARI, 2022)
Waste is an unwanted residual material after the end of a certain process. Where waste in processes that exist in nature, there is actually no concept of waste but only the products that are produced after and during the process in nature. There are various processes that can be applied to produce RDF, including through biodrying. Biodrying itself is one part of the Mechanical-Biological Treatment (MBT) technology which aims to reduce the water content in the waste by utilizing the heat generated by the activity of microorganisms in degrading organic matter so that there is an increase in calorific value. Therefore, the purpose of this study was to analyze the level of response of students from the University of Jember to waste processing into refuse derived fuel (rdf) with biodrying treatment. This research method uses a survey with 30 respondents each from class, 2019, 2020 and 2021. The variable of this research is the critical thinking ability of Jember University students towards waste management into refuse derived fuel (rdf) with biodrying treatment. The results of the questionnaire were analyzed to determine the level of critical thinking of students at the University of Jember towards waste processing into refuse derived fuel (rdf) with biodrying treatment. The results of this study show that the average score for the critical thinking ability of Physics Education students in the Class of 2019 is 35.90, the Class of 2020 is 36.27 and the Class of 2021 is 34.07. It can be interpreted that the average score of the results of the critical thinking ability of Physics Education students for the Class of 2019 <Class of 2020> from the Class of 2021, then there is a difference in the average value of critical thinking skills between the Class of 2019, Class of 2020 and Class of 2021. Keywords : Student Crisis Thinking Ability, Waste Management, Refuse Derived Fuel (RDF), Biodrying.